The assessment of the physico-chemical, microbiological and kinetic parameters of acidulants used in the production of acidified dried sausages made from the meat of blesbok (Damaliscus pygargus phillipsi) - Van den Honert, Mathew Paul (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScFoodSc)--Stellenbosch University, 2015.